PERSYARATAN PERIZINAN LINGKUNGAN DAN ARTI PENTINGNYA BAGI UPAYA PENGELOLAAN LINGKUNGAN DI INDONESIA - Suparto Wijoyo (Yuridika, 2012)
The functional meaning of environmental license in order to manage environment can be seen on the precision or exactness of fulfillment of conditions of environmental license which administratively is relevant for environmental protection. The conditions, that must be met to hold environmental license, have important meaning to evaluate environmental management conducted by corporation. Conditions of environmental license as inserted in document of license are direction that must be followed by the holder of license. Government institutions which have competence to give license should formulate all aspects of operation of industrial activity in the form environmental license.Keywords: environmental licence, environmental protection, environmental management.